Gingerenone A, a polyphenol present in ginger, suppresses obesity and adipose tissue inflammation in high‐fat diet‐fed mice. Issue 10 (20th July 2017) - Suk, Sujin; Kwon, Gyoo Taik; Lee, Eunjung; Jang, Woo Jung; Yang, Hee; Kim, Jong Hun; Thimmegowda, N. R.; Chung, Min‐Yu; Kwon, Jung Yeon; Yang, Seunghee; Kim, Jason K.; Park, Jung Han Yoon; et al.
Abstract : Scope: Ginger exerts protective effects on obesity and its complications. Our objectives here are to identify bioactive compounds that inhibit adipogenesis and lipid accumulation in vitro, elucidate the anti‐obesity effect of gingerenone A (GA) in diet‐induced obesity (DIO), and investigate whether GA affects adipose tissue inflammation (ATI). Methods and results: Oil red O staining showed that GA had the most potent inhibitory effect on adipogenesis and lipid accumulation in 3T3‐L1 cells among ginger components tested at a single concentration (40 μM). Consistent with in vitro data, GA attenuates DIO by reducing fat mass in mice. This was accompanied by a modulation of fatty acid metabolism via activation of AMP‐activated protein kinase (AMPK) in vitro and in vivo. Additionally, GA suppressed ATI by inhibiting macrophage recruitment and downregulating pro‐inflammatory cytokines. Conclusion: These results suggest that GA may be used as a potential therapeutic candidate for the treatment of obesity and its complications by suppressing adipose expansion and inflammation. Abstract : Gingerenone A (GA), a polyphenol in ginger component, suppresses body weight gain induced by HFD, which primarily involves in a decrease in fat mass. Moreover, GA reduces HFD‐induced macrophage infiltration and adipose tissue inflammation by modulating adipokines in EWAT. These results suggest that GA may be used as a potential therapeutic candidate for the treatment of obesity and its complications by suppressing an increase in fat mass and adipose inflammation.